The Routledge companion to journalism in the global south - Mutsvairo, Bruce; Bebawi, Saba; Borges-Rey, Eddy (Oxon : Routledge, 2024)
"Responding to mounting calls to decenter and decolonize journalism, The Routledge Companion to Journalism in the Global South examines not only the deep-seated challenges associated with the historical imposition of Western journalism standards on constituencies of the Global South but also the opportunities presented to journalists and journalism educators if they choose to partake in international collaboration and education. This collection returns to fundamental questions around the meaning, value, and practices of journalism from alternative methodological, theoretical, and epistemological perspectives. These questions include: What really is journalism? Who gets to, and who is qualified to, define it? What role do ethics play? What are the current trends, challenges, and opportunities for journalism in the Global South? How is news covered, reported, written, and edited in non-Western settings? What can journalism players living and working in industrialized markets learn from their non-Western colleagues and counterparts, and vice versa? Contributors challenge accepted "universal" ethical standards while showing the relevance of customs, traditions, and cultures in defining and shaping local and regional journalism. Showcasing some of the most important research on journalism in the Global South and by journalists based in the Global South, this companion is key reading for anyone researching the principles and practices of journalism from a de-essentialized perspective."--
Keywords: Journalism--Developing Countries